Serum urea/albumin ratio; Covid-19 patients - Musa, Norsyuhadah; Wan Azman, Wan Norlina; Mohammad Nazri, Nor Amirah; Tuan Ismail, Tuan Salwani; Harun, Azian; Yaacob, Najib Majdi; Sulong, Sarina; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Che Mat, Mahaya; Mustapa, Siti Sarah (2022)
Background The blood urea to albumin ratio is an inflammatory biomarker that has been linked to clinical outcomes in a variety of diseases . In this regard, the urea/albumin ratio can be a useful biomarker that allows the clinician to identify those at higher risk of critical illness quickly. This study aims to determine the association between the urea/albumin ratio and severity among COVID-19 patients. Methodology This was a retrospective study on hospitalised adult COVID-19 patients aged 18 to 80 at Hospital Raja Perempuan Zainab II (HRPZ II) between February 2021 and February 2022. A total of 170 COVID-19 patients were enrolled in this study. The serum urea, albumin, and creatinine level on admission were recorded. The patients were classified into five clinical stages based on Annex 2e guidelines by Malaysia's Ministry of Health. The patients were grouped by disease severity into mild to moderate disease (Stage 1-3) and severe to critical illness (Stage 4-5). The statistical analysis was using SPSS version 27. This study was approved by (JEPeM-USM) protocol code USM/JEPeM/21100691 and Ministry of Health Malaysia NMRR-21-762-58458 (IIR). Results and Discussion Of the patients who were included in the study, 56 (32.9%) were mild to moderate category, and 114 (67.1%) were in the severe to the critical group. 69(40.6%) were male, and 101(59.4%) were female. The mean age was significantly higher in the severe to the critical group, 59.26 ± 13.6 years, compared to the mild to moderate group, 52.09 ± 22.2 years, p=0.010. The severe to critical group had a significantly higher median value of urea, creatinine, and urea/albumin ratio compared to the mild to moderate group. (urea: 7.0(7.20) and 3.6(3.2), p<0.001; creatinine 89.50(59.75) and 54.3(39.75), p<0.001; urea/albumin ratio 0.21(0.24) and 0.08(0.07), p<0.001). The mean albumin value in the severe to the critical group was significantly lower than in the mild to moderate group (34.95 ± 5.57 and 37.8 ± 5.58, respectively; p = 0.002). These findings suggest that markers of renal function could reliably identify the risk of COVID-19 in individuals. Conclusion Based on our study findings, a high urea/albumin ratio on admission was associated with severe COVID-19 infection. This biomarker could aid in risk stratification models for predicting serious and fatal outcomes of COVID-19 disease. Further studies are needed to define the optimal cut-off point for this marker and reach a consensus on its prognostic value.